Marine heat waves in the Mediterranean Sea: An assessment from the surface to the subsurface to meet national needs - Dayan, Hugo; McAdam, Ronan; Juza, Mélanie; Masina, Simona; Speich, Sabrina (Frontiers in Marine Science, 2023)
In the Mediterranean Sea, marine ecosystems and the resource-based economy are shared among many countries, making this a regional sea of important geopolitical and economic stakes. Over the last decades, marine heat waves (MHWs) in the Mediterranean Sea have caused mass-mortality events in various marine species and critical losses for seafood industries. MHWs are expected to become more intense, longer and more frequent through anthropogenic warming. This study proposes to better understand how much each Mediterranean country’s Exclusive Economic Zone (EEZ) waters may be affected by MHW changes, to contribute to decision support for management and adaptation at national scale. The variability of surface and subsurface MHWs is assessed over the 1987-2019 period in the Mediterranean EEZs, which are ocean areas where sovereign states have special rights. Combining high-resolution satellite observations and a regional reanalysis, sea surface temperature and ocean heat content are used to define surface and subsurface MHWs. The MHW characteristics selected in this study highlight the important differences between surface and subsurface extreme events. MHW frequency is higher at the surface than in the subsurface and has significantly increased in most EEZs both at the surface and in the subsurface, while MHW duration is longer in the subsurface than at the surface in all EEZs. MHW intensities decrease with depth, while its increase over time is more disparate throughout the basin. MHW maximum intensity displays significant positive trends with higher surface values in the western Mediterranean Sea, while in the subsurface it reaches its extreme values in the EEZs of the Levantine basin. In contrast, MHW cumulative intensity exhibits its extreme trend values in the eastern Mediterranean Sea both at the surface and in the subsurface. The choice of a “Top-Ten” list of EEZs shows that the impact to EEZs is different depending on the MHW characteristics and the depth, emphasizing the need to consider all MHW characteristics and to avoid focusing only on the surface. Overall, the results highlight the necessity of strengthening surface and subsurface observing systems in most national waters to better establish local-scale risk assessments and to respond to diverse stakeholder needs.